Curvatura en teorías generalizadas de Yang-Mills - Chaves, Max (2009)
The curvature in R1+3 spaces with a generalized Yang-Mills connection is studied and the results are analyzed. Other options borne by modifications of the base space are also studied and commented. The present situation of the problem is reviewed.